Criminal Liability for Cyberbullying Perpetrators from the Perspective of Indonesian Criminal Law - Fadilla Dwi Maharani; Padrisan Jamba (Sean Institute, 2026)
Cyberbullying is one form of crime in the digital space that has serious impacts on victims, both psychologically, socially, and economically. The characteristics of this crime, such as the anonymity of perpetrators, its wide reach, and the rapid dissemination of information, pose distinct challenges to the enforcement of criminal law. This study aims to analyze the criminal liability of cyberbullying perpetrators from the perspective of Indonesian criminal law and to identify obstacles in efforts to provide legal protection for victims.The research method employed is a normative juridical approach through library research, conducted by examining statutory regulations, legal doctrines, and relevant literature. The results of the study indicate that criminal liability for cyberbullying perpetrators is fundamentally supported by existing legal frameworks, primarily through Law Number 11 of 2008 on Electronic Information and Transactions, as amended by Law Number 19 of 2016, as well as provisions in the Indonesian Criminal Code, particularly Articles 310 and 311 concerning defamation. Nevertheless, the implementation of these legal provisions continues to face various obstacles, including the limited understanding of law enforcement officials, difficulties in digital evidence collection, technological developments that are not balanced with regulatory updates, and the low level of public awareness in reporting cases. Therefore, more comprehensive efforts are required through regulatory strengthening, capacity building for law enforcement authorities, inter-agency cooperation, and digital education and literacy to ensure effective legal protection for victims of cyberbullying in Indonesia.